Doping and Switchable Photovoltaic Effect in Lead‐Free Perovskites Enabled by Metal Cation Transmutation. Issue 34 (5th July 2018) - Harikesh, Padinhare Cholakkal; Wu, Bo; Ghosh, Biplab; John, Rohit Abraham; Lie, Stener; Thirumal, Krishnamoorthy; Wong, Lydia Helena; Sum, Tze Chien; Mhaisalkar, Subodh; Mathews, Nripan
Abstract: Creating defect tolerant lead‐free halide perovskites is the major challenge for development of high‐performance photovoltaics with nontoxic absorbers. Few compounds of Sn, Sb, or Bi possess ns 2 electronic configuration similar to lead, but their poor photovoltaic performances inspire us to evaluate other factors influencing defect tolerance properties. The effect of heavy metal cation (Bi) transmutation and ionic migration on the defects and carrier properties in a 2D layered perovskite (NH4 )3 (Sb(1− x ) Bi x )2 I9 system is investigated. It is shown, for the first time, the possibility of engineering the carriers in halide perovskites via metal cation transmutation to successfully form intrinsic p‐ and n‐type materials. It is also shown that this material possesses a direct–indirect bandgap enabling high absorption coefficient, extended carrier lifetimes >100 ns, and low trap densities similar to lead halide perovskites. This study also demonstrates the possibility of electrical poling to induce switchable photovoltaic effect without additional electron and hole transport layers. Abstract : The effect of heavy metal cation (Bi) transmutation and ionic migration on the defects and carrier properties in a 2D layered perovskite (NH4 )3 (Sb(1− x ) Bi x )2 I9 system is investigated. This transmutation enables the formation of intrinsic p‐ and n‐type materials with a direct–indirect bandgap, extended carrier lifetimes >100 ns and low trap densities similar to lead halide perovskites. It is also shown that this material exhibits a switchable photovoltaic effect without additional electron and hole extraction layers.